Biochar Amendment Reduces the Availability of Pb in the Soil and Its Uptake in Lettuce - Andrea Vannini; Elisabetta Bianchi; Diego Avi; Nicole Damaggio; Luigi Antonello Di Lella; Francesco Nannoni; Giuseppe Protano; Stefano Loppi (Toxics, 2021)
The aim of this study was to investigate the ability of biochar amendment to reduce the availability of Pb in the soil and its uptake in lettuce (Lactuca sativa L. var. adela). Seedlings of lettuce were cultivated in Pb-contaminated soils, both with and without 5% biochar (w/w), as well as in a simplified soilless system (hydroponics) at the ecologically relevant Pb concentration of 100 µM, both with and without 1% biochar. Soils amended with biochar resulted in a ca. 50% reduction of the extractable (bioavailable) fraction of Pb, limiting the accumulation of this toxic element in the leaves of lettuce by ca. 50%. A similar behavior was observed for lettuce plants grown hydroponically, even with a much higher reduction of Pb uptake (ca. 80%). Increased cation exchange capacity and pH were likely the main factors limiting the bioavailability of Pb in the soil. Complexation with functional groups and precipitation/co-precipitation both on the biochar surface and in soil aggregates were likely the main mechanisms immobilizing this element.